Empowerment of The Farmer Group Bisimo Etaikena in Managing Pig Livestock Waste to Become Organic Fertilizer - Tuhuteru, Sumiyati; Mahanani, Anti Uni; Rumbiak, Rein Edward Yohanes; Sutiknyawati Kusuma Dewi, Yohana; Inrianti, Inrianti; Tabuni , Endius; Tabo, Opapur; Doga , Konius; Wenda, Endison; Lengka , Mariana; Himan , Rusina (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2023)
Background: The conversion of livestock manure into organic fertilizer is quite safe and not difficult to do. Compost is believed to improve soil texture by making the soil more friable. In order to increase food security and raise awareness of the value of health and the beauty of the environment for farmer groups that raise pigs, this activity aims to increase the knowledge and skills of farmers in Husoak Village. Contribution: Provide knowledge and enhance abilities for turning pig manure into compost that is good for cultivated plants, in increasing food security and farmers' knowledge about the importance of health and sustainability. Method: Conversation, Observation, and Socialization, providing assistance, engaging in manufacturing, and documenting Results: As evidenced by the number of farmers applying it—5 in total with 1 farmer serving as a pioneer in adopting the use of pig waste compost, which reduces odor pollution—the use of pig manure as compost is succeeding. Conclusion: that the compost processing training was completed within a month as planned, with the use of pig waste compost being observed in 5 farmers who had implemented the processing of pig manure into compost and had consumed the harvested products themselves. The next suggestion is to expand the use of composted pig manure as an agricultural input to ensure the sustainability of community agriculture